Human Rights, Refugees and Internally Displaced Persons: The UN Commission on Ruman Rights - Tim Wichert (Refuge, 1997)
This article argues that protecting refugees and internally displaced persons (IDPs) is an issue of universal human rights. It then suggests the urgent need for the UN Commission on Human Rights, working in collaboration with the United Nations High Commissioner for Refugees (UNHCR) and member states of the United Nations, to play more important roles in protecting and enhancing human rights. It also stresses the importance of appropriate follow-up to the calls for more commitment and better actions in this area.